Zircon radiation damage ages - Pidgeon, Robert (Elsevier Science BV, 2014)
The suggestion that the accumulation of radiation damage in zircons could be used as a dating method was first proposed in the 1950s. In the original technique radiation damage was determined by X-ray diffraction however, this is not suitable for the small sample analysis needed in modern geochronology. It is now possible to measure radiation damage and U and Th contents on micron-sized areas on the polished surface of zircon grains using Raman spectroscopy and SIMS mass spectrometry. This opens the way for a reassessment of the potential of radiation damage ages and the purpose of this contribution is to re-examine the technique through its application to zircons from two granitoids from the Archean Yilgarn Craton and ancient detrital zircons from the Jack Hills in Western Australia. The three examples show internally consistent radiation damage ages that are also in accord with independent geochronological evidence. The 420 ± 110 Ma radiation damage age for the Darling Range granite is coincident with 500–400 Ma biotite Rb–Sr ages in the same region of the Yilgarn Craton. Likewise a tonalite from the Youanmi Terrane in the Craton with a 1650 ± 150 Ma zircon radiation damage age, lies within the domain of a 1600 Ma event recorded by biotite Rb–Sr ages. The Jack Hills zircons have a 1120 ± 130 Ma radiation damage age that is explained by a complex damage accumulation and annealing history culminating in a mild heating event indicated by biotite Ar–Ar ages of about 1140 Ma. The positive results for the three case histories suggest that radiation damage ages could play a useful role in dating low temperature thermal events.